Phosphatidylglycerol is implicated in divisome formation and metabolic processes of cyanobacteria - Kóbori, Tímea O; Uzumaki, Tatsuya; Kis, Mihály; Kovács, László; Domonkos, Ildikó; Itoh, Shigeru; Krynická, Vendula; Kuppusamy, Saravanan G; Zakar, Tomas; Dean, Jason; Szilák, László; Komenda, Josef; et al. (Journal of plant physiology, 2018)
Phosphatidylglycerol is an essential phospholipid for photosynthesis and other cellular processes. We investigated the role of phosphatidylglycerol in cell division and metabolism in a phophatidylglycerol-auxotrophic strain of Synechococcus PCC7942. Here we show that phosphatidylglycerol is essential for the photosynthetic electron transfer and for the oligomerisation of the photosynthetic complexes, notably, we revealed that this lipid is important for non-linear electron transport. Furthermore, we demonstrate that phosphatidylglycerol starvation elevated the expressions of proteins of nitrogen and carbon metabolism. Moreover, we show that phosphatidylglycerol-deficient cells changed the morphology, became elongated, the FtsZ ring did not assemble correctly, and subsequently the division was hindered. However, supplementation with phosphatidylglycerol restored the ring-like structure at the mid-cell region and the normal cell size, demonstrating the phosphatidylglycerol is needed for normal septum formation. Taken together, central roles of phosphatidylglycerol were revealed; it is implicated in the photosynthetic activity, the metabolism and the fission of bacteria.
Keywords: Phosphatidylglycerol; Photosynthesis; transport elektronů; Electron transport; fosfatidylglyceroly; Division; Cell Division; Photosystem I Protein Complex; Lipid; Synechococcus; Electron Transport; fotosystém I (proteinový komplex); Phosphatidylglycerols; buněčné dělení